Infection and undernutrition increase the risk of stunting among rural children - Akrom Akrom; Titiek Hidayati; Olyvia Wulan Kencana; Nurcholid Umam Kurniawan; Prasasti Bintarum (International Journal of Public Health Science (IJPHS), 2022)
The prevalence of stunting in Indonesia is remaining high. Stunting is found to be more common in rural areas than in urban areas. This study aimed to determine the factors associated with stunting in rural areas. We conducted a case-controlled study in Public Health Center Jetis 1 Yogyakarta, Indonesia. We recruited 80 children with the purposive sampling technique. Data on birth weight and disease history were taken from their medical records. Data on consumption patterns of energy, protein, carbohydrate, and fat were collected through a nutritional survey. Different proportions were tested using the fisher test and the mean difference was tested using an independent t-test. The results showed that child stunting had lower energy and protein consumption levels than non-stunting children (p=0.000). Diarrheal infection, frequency, and duration of illness were more common in stunted than in non-stunted children (p<0.05). Consumption of protein and energy was associated with stunting (p<0.05). This research found differences in the incidence of infection, frequency, length of illness, and hospital stay between stunted and non-stunted children. There is a significant association between the consumption of protein and energy with stunted growth in children in rural public health children.